(untitled) - Snow, Roberta (San Francisco, 2008)
Making Critical Decisions offers nonprofit leaders a proven model for making hard choices that minimize risks while maintaining progress toward the organization’s goals as well as a practical framework for understanding and implementing the decision-making process. The book includes qualitative and quantitative tools and offers illustrative case examples throughout that clearly show how this method can be applied to different types of nonprofit organizations
Keywords: Decision making,Nonprofit organizations,Ra quyết định,Tổ chức phi lợi nhuận; Management,quản lý